Awareness and practices regarding post-partum diet among post-natal mothers - Paliwal, Haribala; Zachariah, Jisha; Nagda, Sanjay; Paliwal, Chetna; Chaturvedi, Dharmesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Postnatal mothers need about 500 extra calories each day, as well as plenty of protein, calcium and fluids to stay healthy and produce nutritious breast milk. Balanced diet during puerperal period must include lean meats, high-fiber foods, low-fat dairy products and plenty of fresh fruits and vegetables. Therefore, present study aims to assess the knowledge and dietary practices among the women during their puerperal period. Method: Quantitative descriptive research design was utilized to carry out the study. A sample of women during their puerperal period admitted in district hospital, Tumkur, Karnataka, selected for the study using non probability convenient sampling technique. Results: Study found that 87% participants had average and poor knowledge while 82% participants had average and poor practices regarding post-partum diet during their puerperal period. Age, educational status, occupational status, monthly income, type of family, obstetrical score, source of information from T.V., book and newspaper were significantly associated with knowledge score. Religion, educational status, occupational status, monthly income, place of residence, source of information from T.V., book, newspaper, friends and relatives were significantly associated with the practice score of the participants. There was significant correlation (r=0.304) found between knowledge and practice score regarding post-partum diet among participants. Conclusions: Study concluded that there was less knowledge and poor practice among majority of the postnatal mothers regarding post-partum diet. Hence, proper awareness regarding importance of balanced post-partum diet must be given to the post-natal mothers.